PENGARUH HIDROLISIS TERHADAP PRODUKSI BIOETANOL DARI LIMBAH KULIT JERUK DAN DAUN JAMBU BIJI - Muhammad Nur Alam; Sartika Suardi; Ilmiati Illing (Universitas Cokroaminoto Palopo, 2022)
The increase in population causes an increase in transportation and industrial facilities which results in high demand and consumption of fuel oil (BBM). Therefore, alternative renewable energy sources are needed. One of the alternatives is bioethanol from orange peel waste (Citrus x sinensis) and guava leaves (Psidium Guajava). This study aims to determine how to make bioethanol from sweet orange peel waste and guava leaves and to determine the amount of ethanol produced. Orange peels (Sitrus xsinensis) and guava leaves (Psidium guajava) are commonly found in various areas, especially in Luwu and North Luwu regencies which can be used as alternative fuels. The methods in this study include the manufacture of flour, hydrolysis (for sample A1). The addition of distilled water without hydrolysis (for sample A2), fermentation and distillation to produce 4 ml of ethanol in sample A1. The drawback of this study is that sample A2 does not produce ethanol because the fermentation lasts too long so that the alcohol turns into ester compounds